ORGANISASI KERJASAMA GLOBAL: PERAN ASEAN DAN UNICEF DALAM PENINGKATAN KUALITAS PENDIDIKAN - Ummu Hafifah; Sisnadia Rahmawati, Desti Rahmawati, Feriska Listy, Masramita, Yoga Fernando Rizqi (CV. ADIBA AISHA AMIRA, 2024)
Improving the quality of education is very important because it helps students prepare themselves to achieve success in the future and helps build a better society. In this research the author used qualitative methods. This research aims to observe the collaborative efforts of ASEAN and UNICEF in identifying education problems and the role of the two organizations in efforts to improve the quality of education. The collaboration between these two organizations has had a positive impact in improving educational accessibility, educational quality and educational relationships for children. The policy implementation resulting from this research provides valuable insights for policymakers to strengthen partnerships and joint efforts in improving education systems in Southeast Asia.